Kajian Pemikiran Konsep Tasawuf Insan Kamil Muhammad Nafis al-Banjari Dalam Kitab ad-Durr an-Nafis - Mochammad Harun Rosyid (Raudhatun Najah Publisher, 2022)
The study of the concept of insan kamil (the perfect man) is a study that is very often discussed in Sufism. The concept of insan kamil that emerged in the world of Sufism in the VII H century eventually developed in Islamic thought to the Archipelago. Because many discoveries from the books written by the Sufis. There is some evidence of Sufis who study this theme, namely Muhammad Nafis al-Banjari in his book ad-Durr an-Nafis and Abd al-Karim al-Jili in his book al-Insan al-Kamil fi Ma’rifat al-Awakhir wa al-Awa' il. Muhammad Nafis al-Banjari was not the first originator of the concept of insan kamil because several scholars have discussed the concept of insan kamil such as Ibn ‘Arabi, al-Hallaj, al-Suhrawardi, at-Tirmidhi. The book of ad-Durr an-Nafis has clarity and ways in the formation of human beings with religious values. Insan kamil can be formed if humans respect each other and carry out their religious teachings purely and consistently. This paper aims to explain and provide a good understanding of the concept of insan kamil from the book ad-Durr an-Nafis.